miR-124 Alleviates Ischemic Stroke-Induced Neuronal Death by Targeting DAPK1 in Mice - Shi, Yan; Tian, Tian; Cai, Er-Li; Yang, Can; Yang, Xin (Frontiers in Neuroscience, 2021)
Background: Ischemic stroke induces neuronal cell death and causes brain dysfunction. Preventing neuronal cell death after stroke is key to protecting the brain from stroke damage. Nevertheless, preventative measures and treatment strategies for stroke damage are scarce. Emerging evidence suggests that microRNAs (miRNAs) play critical roles in the pathogenesis of central nervous system (CNS) disorders and may serve as potential therapeutic targets. Methods: A photochemically induced thrombosis (PIT) mouse model was used as an ischemic stroke model. qRT-PCR was employed to assess changes in miRNAs in ischemic lesions of PIT-stroke mice and primary cultured neurons subjected to oxygen-glucose deprivation (OGD). 2,3,5-triphenyltetrazolium chloride (TTC) staining was performed to evaluate brain infarction tissues in vivo. TUNEL staining was employed to assess neuronal death in vitro. Neurological scores and motor coordination were investigated to evaluate stroke damage, including neurological deficits and motor function. Results: In vivo and in vitro results demonstrated that levels of miR-124 were significantly decreased following stroke, whereas changes in DAPK1 levels exhibited the converse pattern. DAPK1 was identified as a direct target of miR-124. N-methyl-D-aspartate (NMDA) and OGD-induced neuronal death was rescued by miR-124 overexpression. Upregulation of miR-124 levels significantly improved PIT-stroke damage, including overall neurological function in mice. Conclusions: We demonstrate the involvement of the miR-124/DAPK1 pathway in ischemic neuronal death. Our results highlight the therapeutic potential of targeting this pathway for ischemic stroke.